The Backwash Effect of Post-Graduate Study Entrance Test on English Competence of Candidate Academics - Deastika Bayuning Sudjasmara (Ma'soem University, 2021)
This research is a case study at an education university in Bandung. It is conducted to investigate whether post-graduate entrance tests on English competence create any backwash effect on candidate academics learning behavior and identify how the test shapes the learning experience. This research employs a case study with qualitative approach, involving 25 newly graduated bachelor degree students of five different departments of an education university in Bandung. Questionnaire is employed to gain the data. The results reveal that regarding the type of the test, post-graduate entrance test has a positive effect on candidate academics. This kind of test types leads the candidate academics to a positive language learning behavior. The candidate academics spend more time in studying and prepare the test by practicing reading comprehension, vocabulary, and grammar. However, the type of the test which is in the form of multiple-choice directs point of view of the learners on the tests to be negative since the test doesn’t represent the candidate academics’ skills.